AQP3 is regulated by PPARγ and JNK in hepatic stellate cells carrying PNPLA3 I148M. Issue 1 (December 2017) - Tardelli, Matteo; Bruschi, Francesca; Claudel, Thierry; Moreno-Viedma, Veronica; Halilbasic, Emina; Marra, Fabio; Herac, Merima; Stulnig, Thomas; Trauner, Michael
Abstract Aquaglyceroporins (AQPs) allow the movement of glycerol that is required for triglyceride formation in hepatic stellate cells (HSC), as key cellular source of fibrogenesis in the liver. The genetic polymorphism I148M of the patatin-like phospholipase domain-containing 3 (PNPLA3) is associated with hepatic steatosis and its progression to steatohepatitis (NASH), fibrosis and cancer. We aimed to explore the role of AQP3 for HSC activation and unveil its potential interactions with PNPLA3. HSC were isolated from human liver, experiments were performed in primary HSC and human HSC line LX2. AQP3 was the only aquaglyceroporin present in HSC and its expression decreased during activation. The PPARγ agonist, rosiglitazone, recovered AQP3 expression also in PNPLA3 I148M carrying HSC. When PNPLA3 was silenced, AQP3 expression increased. In liver sections from patients with NASH, the decreased amount of AQP3 was proportional to the severity of fibrosis and presence of the PNPLA3 I148M variant. In PNPLA3 I148M cells, the blockade of JNK pathway upregulated AQP3 in synergism with PPARγ. In conclusion, we demonstrated profound reduction of AQP3 in HSC carrying the PNPLA3 I148M variant in parallel to decreased PPARγ activation, which could be rescued by rosiglitazone and blockade of JNK.